The Effect of Digital Technology Training on the Competence of Nurses in Telenurse Services - Helsy Desvitasari; Indrawati; Linda Jurwita; Muhammad Husaini; A wardah Muzfah (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
the development of digital technology has changed the paradigm of health care, including in the practice of Telenurse, where nurses are required to have sufficient digital competence to provide remote services effectively. Purpose: This study purpose to determine the effect of digital technology training on the competence of nurses in Telenurse services. Methods: this study uses quasi-experimental quantitative design with pretest-posttest approach. The sample consisted of 20 purposively selected nurses at Hermina Hospital Pekanbaru. Data were collected using the nurse digital competency questionnaire and analyzed using the Wilcoxon test to determine significant differences in competency before and after training, because the sample size is relatively small and the data is not always normally distributed. Results: the results showed a significant increase in nurse competence after training, with an average pretest value of 60.5 increased to 82.3 on the posttest (p < 0.05). These improvements include aspects of mastering Telenurse applications, digital communication with patients, and technical troubleshooting. Conclusion: digital technology training effectively improves the competence of nurses in Telenurse services, thus enabling more efficient, accurate, and responsive services. The implications of this study emphasize the importance of continuous training programs for nurses to master digital technology, as well as hospital management support in the provision of adequate facilities and Telenourse systems to improve the quality of health services.